Pelatihan Pelatihan Literasi Kesehatan Mental Pada Komunitas Guru Bimbingan dan Konseling di Kota Surakarta - Yulianti, Padmi Dhyah; Fajriyah, Khusnul; Putriyanti, Lina; Setianingsih, Eka Sari (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
Generation Z grows up in a dynamic digital ecosystem that presents unique challenges for the education sector, particularly in learning styles and psychosocial needs. This situation requires guidance and counseling (GC) teachers not only to be adaptive to technological advances but also to possess adequate mental health literacy to provide optimal services. At the same time, GC teachers themselves are vulnerable to psychological pressures due to heavy workloads. The Association of Guidance and Counseling Teachers (MGBK) plays a strategic role in strengthening teachers’ professionalism while encouraging them to become agents of change in promoting students’ mental health. This community service program aimed to enhance GC teachers’ knowledge and skills through mental health literacy training. The training was conducted on April 23, 2025, at the hall of SMA Negeri 1 Surakarta, involving GC teachers from high schools across Surakarta City who are members of MGBK. The program consisted of a pretest, material delivery, and posttest. Training materials covered fundamental concepts of mental health literacy, promotive and preventive strategies, skills in early detection and initial intervention, strengthening counseling services to support school programs and character building, as well as developing empathetic communication skills in counseling sessions. The results showed an increase in teachers’ knowledge and awareness of mental health issues in schools. These findings highlight the effectiveness of the training in enhancing the competencies of GC teachers as school-based mental health agents. In the future, continuous mentoring and the integration of mental health literacy into technology-based counseling services are needed to better address the needs of 21st-century students.